The PENINGKATAN KAPASITAS MANAJERIAL UMKM DI KELURAHAN TAPPANJENG KECAMATAN BANTAENG KABUPATEN BANTAENG: PENINGKATAN KAPASITAS MANAJERIAL UMKM DI KELURAHAN TAPPANJENG KECAMATAN BANTAENG KABUPATEN BANTAENG - Syamsul Alam; Maryadi Maryadi; Muhammad Idris; Sylvia Sylvia; M. Salim Sultan (ADPERTISI, 2022)
The MSME sector has a strategic role in the national economy but in its development there are still many obstacles. Therefore, this Community Service activity is directed to achieve the following objectives: 1) Providing insight or additional knowledge to MSME actors in Tappanjeng Village regarding good business governance, 2) Providing counseling on marketing techniques, financial management, developing business networks; 3) Provide insight into the importance of promoting using social media. After carrying out community service activities, several important points to be recommended are: 1) This training activity still needs to be continued in the form of mentoring to ensure the achievement of the overall service goals; 2) It takes the involvement of many parties in order to encourage the improvement of the managerial capabilities of MSME actors. Both the local government, banks, universities, and other non-governmental organizations.